2021
DOI: 10.3389/fonc.2021.716152
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison, Treatment Efficiency Estimation, and Biological Evaluation of Popular Stereotactic Radiosurgery Options in Treating Single Small Brain Metastasis

Abstract: ObjectivesThis study aimed to show the advantages of each stereotactic radiosurgery (SRS) treatment option for single small brain metastasis among Gamma Knife (GK), Cone-based VMAT (Cone-VMAT), and MLC-based CRT (MLC-CRT) plans.Materials and MethodsGK, Cone-VMAT, and MLC-CRT SRS plans were retrospectively generated for 11 patients with single small brain metastasis whose volume of gross tumor volume (GTV) ranged from 0.18 to 0.76 cc (median volume 0.60 cc). Dosimetric parameters, treatment efficiency, and biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…In the future, we can evaluate the impact of different algorithms on patient clinical outcomes through long-term multi-institutional follow-up observations. Furthermore, utilizing the built-in biological assessment module in TPS, evaluating the impact of different algorithms on tumor control probability (TCP) and normal tissue complications probability (NTCP) in terms of dose differences is considered a future research direction ( 33 , 37 , 38 ). This study can assist radiation oncologists in prospectively understanding the impact of these three algorithms on patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we can evaluate the impact of different algorithms on patient clinical outcomes through long-term multi-institutional follow-up observations. Furthermore, utilizing the built-in biological assessment module in TPS, evaluating the impact of different algorithms on tumor control probability (TCP) and normal tissue complications probability (NTCP) in terms of dose differences is considered a future research direction ( 33 , 37 , 38 ). This study can assist radiation oncologists in prospectively understanding the impact of these three algorithms on patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another common SRS modality is Gamma-Knife radiosurgery (GK). The outcome from a study conducted in China revealed applicable of Cone-based VMAT in a GK-free RT center [ 18 ]. They retrospectively analyzed dosimetric comparison between GK, Cone-based VMAT, and MLC-based conformal radiotherapy for small single brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…They retrospectively analyzed dosimetric comparison between GK, Cone-based VMAT, and MLC-based conformal radiotherapy for small single brain metastases. The result showed better CI and HI, similar GI, but longer beam-on time for GK compared to Cone-based approach [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of hypofractionation did not correlate with a high metastasis size because some studies used a single fraction even for large targets. Consequently, intervals of BM's size treated with single and three fractions overlapped (0.01-29.18 cc and 10.5-21.4 cc, respectively) [19][20][21][22][23][24][25][26][27][28][29]. which 10 were duplicates.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…The dose and isodose prescriptions lacked homogeneity as well. Nine studies used SRS [21][22][23][24][25][26][27][28][29] and only two studies used HF-SRT [19,20]. The choice of hypofractionation did not correlate with a high metastasis size because some studies used a single fraction even for large targets.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%